Case Study: Application Development with ATaG - Bakshi, Amol B; Prasanna, Viktor K (Architecture-Independent Programming for Wireless Sensor Networks, 2007)
This chapter contains sections titled: Overview of the Use Case Designing the Macroprograms Specifying the Declarative Portion Imperative Portion: Temperature Gradient Monitoring Imperative Portion: Object Detection and Tracking Application Composition Software Synthesis